Analysis of the Production Process, Income, and Distribution of Rice Seeds from the Seed Management Unit (UPBS) at the Wawotobi Experimental Farm in Konawe Regency - Triwijoyo, Narto; Fausayana, Ine; Rosmawaty (International journal of technology and education research, 2026)
This study aims to 1) Determine the production process of certified rice seeds at the Wawotobi experimental garden, 2) See the income obtained by the Wawotobi experimental garden from the sale of certified rice seeds during one harvest period, 3) Determine the distribution flow carried out by the Wawotobi experimental garden for harvested rice seeds. This study was conducted from July to December 2025. The determination of the research location was determined purposively. The research sample was determined purposively, namely the UPBS manager and technical staff directly involved in seed production and distribution activities. Data analysis was carried out using qualitative descriptive methods to describe the seed production and distribution process, as well as quantitative descriptive methods to analyze income through calculating the difference between revenue and production costs. The results of the study indicate that the certified rice seed production process at the UPBS Wawotobi Experimental Garden has been carried out in accordance with certification standards, starting from land preparation, selection of superior varieties, nurseries, planting, plant maintenance, roguing, harvesting, post-harvest processing, to laboratory testing and labeling. UPBS's revenue from the sale of certified rice seeds during a single harvest period is Rp20.185.938. Seed distribution is carried out through direct sales to farmers and breeders, as well as through grants to support government programs and the dissemination of new superior varieties